SARS-CoV-2 activates the TLR4/MyD88 pathway in human macrophages: A possible correlation with strong pro-inflammatory responses in severe COVID-19 - Sahanic, Sabina; Hilbe, Richard; Dünser, Christina; Tymoszuk, Piotr; Löffler-Ragg, Judith; Rieder, Dietmar; Trajanoski, Zlatko; Krogsdam, Anne; Demetz, Egon; Yurchenko, Maria; Fischer, Christine; Schirmer, Michael; et al. (Heliyon, 2023)
Toll-like receptors (TLRs) play a pivotal role in the immunologic response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Exaggerated inflammatory response of innate immune cells, however, may drive morbidity and death in Coronavirus disease 19 (COVID-19). We investigated the engagement of SARS-CoV-2 with TLR4 in order to better understand how to tackle hyperinflammation in COVID-19. We combined RNA-sequencing data of human lung tissue and of bronchoalveolar lavage fluid cells derived from COVID-19 patients with functional studies in human macrophages using SARS-CoV-2 spike proteins and viable SARS-CoV-2. Pharmacological inhibitors as well as gene editing with CRISPR/Cas9 were used to delineate the signalling pathways involved. We found TLR4 to be the most abundantly upregulated TLR in human lung tissue irrespective of the underlying pathology. Accordingly, bronchoalveolar lavage fluid cells from patients with severe COVID-19 showed an NF-κB-pathway dominated immune response, whereas they were mostly defined by type I interferon signalling in moderate COVID-19. Mechanistically, we found the Spike ectodomain, but not receptor binding domain monomer to induce TLR4-dependent inflammation in human macrophages. By using pharmacological inhibitors as well as CRISPR/Cas9 deleted macrophages, we identify SARS-CoV-2 to engage canonical TLR4-MyD88 signalling. Importantly, we demonstrate that TLR4 blockage prevents exaggerated inflammatory responses in human macrophages infected with different SARS-CoV-2 variants, including immune escape variants B.1.1.7.-E484K and B.1.1.529 (omicron). Our study critically extends the current knowledge on TLR-mediated hyperinflammatory responses to SARS-CoV-2 in human macrophages, paving the way for novel approaches to tackle severe COVID-19. Our study combining human lung transcriptomics with functional studies in human macrophages clearly supports the design and development of TLR4 - directed therapeutics to mitigate hyperinflammation in severe COVID-19. •TLR4 is the most abundantly upregulated TLR in human lung irrespective of the underlying pathology.•BALF MΦ from patients with severe COVID-19 show strong upregulation of the NF-κB pathway.•The ectodomain of the SARS-COV-2 spike protein leads to TLR4 dependent upregulation of IL-6.•Viable SARS-CoV-2 leads to TLR4 dependent IL-6 upregulation irrespective of the variant of concern.•TLR4 inhibition in SARS-CoV-2 infected MΦ leads to downregulation of genes involved in leukocyte migration.